Ontogenesis of NADPH-diaphorase positive neurons in guinea pig neocortex - Liu, Chao; Yang, Yan; Hu, Xia; Li, Jian-Ming; Zhang, Xue-Mei; Cai, Yan; Li, Zhiyuan; Yan, Xiao-Xin (Frontiers in Neuroanatomy, 2015)
In mammalian cerebrum there exist two distinct types of interneurons expressing nitric oxide synthase (NOS). Type I neurons are large in size and exhibit heavy nicotinamide adenine dinucleotide phosphate diaphorase (NADPH-d) histochemical reaction, while type II cells are small with light NADPH-d reactivity. The time of origin of these cortical neurons relative to corticogenesis remains largely unclear among mammals. Here we explored this issue in guinea pigs using cell birth-dating and double-labeling methods. Bromodeoxyuridine (BrdU) pulse-chasing (2 doses at 50 mg/kg, 12 hours apart) was given to time-pregnant mothers, followed by quantification of NADPH-d/BrdU colocalization in the parietal and temporal neocortex in offspring at postnatal day 0 (P0), P30 and P60. Type I neurons were partially colabeled with BrdU at P0, P30 and P60 following pulse-chasing at embryonic day 21 (E21), E28 and E35, varied from 2% to 11.3% of total population of these neurons for the three time groups. Type II neurons were partially colabeled for BrdU following pulse-chasing at E21, E28, E35 and E42 at P0 (8.6%-16.5% of total population for individual time groups). At P60, type II neurons were found to co-express BrdU (4.8%-11.3% of total population for individual time groups) following pulse-chasing at E21, E28, E35, E42, E49, E56 and E60/61. These results indicate that in guinea pigs type I neurons are generated during early corticogenesis, whereas type II cells are produced over a wide prenatal time window persisting until birth. The data also suggest that type II nitrinergic neurons may undergo a period of development/differentiation, for over one month, before being NADPH-d reactive.